Disorienting fiction : the autoethnographic work of nineteenth-century British novels - Buzard, James (Princeton University Press, 2005)
This book gives a revisionist account of the nineteenth-century British novel and its role in the complex historical process that ultimately gave rise to modern anthropology's concept of culture and its accredited researcher, the Participant Observer. Buzard reads the great nineteenth-century novels of Charles Dickens, Charlotte Brontë, George Eliot, and others as "metropolitan autoethnographies" that began to exercise and test the ethnographic imagination decades in advance of formal modern ethnography--and that did so while focusing on Western European rather than on distant Oriental subjects. --From publisher's description.